ANALYSIS ON AlMg2 AS RSG-GAS CLADDING MATERIAL CORROSION IN CHLORIDE CONTAINING WATER - Febrianto Bahar; Sriyono Sriyono; Geni Rina Sunaryo (GANENDRA Majalah IPTEK Nuklir, 2018)
AnalYsis On AlMg2 AS RSG-GAS CLADDING material corrosion IN CHLORIDE CONTAINING WATER. The AlMg2is one of an alluminium alloy that used as cladding material for the RSG GA. Siwabessy (RSG-GAS) research reactor in Serpong, Indonesia. The reactor uses demineralized water as primary coolant with 6.5 to 7.5 of pH. A poor treatment of water in primary coolant can lead to the problem of AlMg2 integrity. The primary coolant concentration of chloride must lower than 0.0094 ppm to protect cladding corrosion. The purpose of this study is to determine the effect of temperature and chloride ion concentration to AlMg2. The method in this research is to observe the corrosion rate for AlMg2 material by using Potentiostat. The laboratory experiments were conducted in various temperatures (28, 35, 40 and 45°C) and concentration of sodium chloride of 0.005, 0.010, 0.015, 0.020, 0.025, 0.030 and 0.035 ppm. The results show the corrosion rates were very small, and the highest corrosion rate occurred is 1.23 x 10-3mpy in 0.035 ppm of NaCl at 45°C .